Increasing trends in hemodialysis and living donor kidney transplantation for children and young people in the United Kingdom. (24th January 2022) - Mudalige, Nadeesha Lakmal; Sun, Kristi; Plumb, Lucy; Casula, Anna; Evans, Katharine M.; Inward, Carol; Marks, Stephen D.
Abstract: Background: The UK Renal Registry is responsible for the national collection and reporting of data on all children receiving long‐term kidney replacement therapy [KRT], including kidney transplantation. Methods: All 13 UK pediatric nephrology centers contributed to providing individual patient data from the pediatric population incident to and prevalent to KRT as per the date 31 December 2018. Data for children aged 16–<18 years were presented separately as some were managed under adult care settings with different methods of data collection. Demographics and biochemical data, including kidney function and prevalence of cardiovascular risk factors [hypertension, hypercholesterolemia, BMI] were reported. Results: Eight hundred and twenty‐six children (65.4 per million age‐related population [pmarp]) and 199 young people (139.4pmarp) in the United Kingdom were prevalent to KRT on 31 December 2018. Overall, the incidence of KRT during 2018 was 9.1 pmarp and 12.6 pmarp in children and young people, respectively. Congenital anomalies of the kidney and urinary tract (CAKUT) were the most prevalent primary diagnoses (52%). Living and deceased donor transplantation was the most common treatment modality (78%). Patients on dialysis had lower age standardized mean height and weight ranges recorded in comparison to transplant patients [median height z score −1.8 vs. −1.1]. 73.1% patients had one or more cardiovascular disease risk factors. Conclusions: This study highlights increasing prevalence of hemodialysis and living donor transplantation as modalities for KRT. Of those incident to KRT, the highest patient survival was seen among 8–12 years and lowest <2 years. Moreover, there was a demographic shift from Caucasian toward Asian/other ethnicity and from CAKUT to other primary kidney diseases.